2010
DOI: 10.3748/wjg.v16.i43.5452
|View full text |Cite
|
Sign up to set email alerts
|

Endotics systemvscolonoscopy for the detection of polyps

Abstract: The ES allows the visualization of the entire colonic mucosa in most patients, with good sensitivity/specificity for the detection of lesions and without requiring sedation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 19 publications
0
38
0
Order By: Relevance
“…The operator can steer the probe head in any direction, elongate the probe body to move it forward, and control rinsing, insufflation, and suction. Small-scale studies have been reported with Endotics, showing superiority in pain reduction versus conventional colonoscopy, but prolonged insertion times and a relatively low cecal intubation rate need to be overcome [ 35 , 36 ].…”
Section: Robotic Colonoscopymentioning
confidence: 99%
“…The operator can steer the probe head in any direction, elongate the probe body to move it forward, and control rinsing, insufflation, and suction. Small-scale studies have been reported with Endotics, showing superiority in pain reduction versus conventional colonoscopy, but prolonged insertion times and a relatively low cecal intubation rate need to be overcome [ 35 , 36 ].…”
Section: Robotic Colonoscopymentioning
confidence: 99%
“…Likewise, the Endotics ® system, that consists of a robotic probe moving forward with an inchworm locomotion, allows for the painless progression into the colon, because it does not create loops, nor cause stretching of the colon walls [57] . The applicability of the Endotics ® system in clinical practice has already been proven [58] , and in 2014 its second version will be marketed with an operative channel of 3 mm in diameter, that will enable to take biopsies and will open the way to perform also other operative maneuvers.…”
Section: New Endoscopic Technologies For Colon Examinationmentioning
confidence: 99%
“…The endotics system was shown to have a sensitivity of 93.3% and a specificity of 100% compared to the gold standard. 44 …”
Section: The Endotics Systemmentioning
confidence: 99%